Theoretical Dialectic of Bureaucracy VS Post-Bureaucracy: Filling the Bureaucracy Gap through the Presence of Post-Bureaucracy - Idrus Mohamad Thomas Mopili; Asna Aneta (GEMA PUBLICA, 2026)
The dialectic between bureaucracy and post-bureaucracy in public administration has given rise to various interpretations that often criticize the limitations  of conventional bureaucracy and encourage the adoption of the post-bureaucracy model. This study aims to analyze the theoretical dialectic between the two paradigms with a focus on identifying gaps in bureaucracy that can be filled through the presence  of post-bureaucracy. The research method used is qualitative with a library research approach, which relies on primary and secondary data sources from related literature. The findings of the study show that  conventional bureaucracy is still needed as a foundation of governance that ensures stability, legal certainty, and procedural accountability. However, in the face of the complexity of the modern environment, this model is considered less responsive to the demands of the dynamics of change, participation, and innovation. This is where post-bureaucracy offers structural flexibility, cross-actor collaboration, digital governance, as well as an orientation to public values. The resulting ideal space is not a substitution, but an integration between the two models: a bureaucracy that maintains rules and accountability, but is flexible and adaptive to change. This synthesis is expected to answer the gap in contemporary public administration and realize stable, inclusive, and responsive governance to the interests of the community.